Optimal location of building transportation systems in large scale shopping malls in Davao City using Dijkstra's Algorithm - Malbas, Maria Agnes R.; Olalo, Kristin Faye M.
In a commercial retail environment, a consumer's experience is highly affected by its retail exposure. The concept of space and how an establishment presents its business can either increase, or decrease, its business revenues. The highly dense areas of a commercial environment gives the shoppers longer exposure to the retail stores within its periphery, while the retail stores in low dense areas have shorter exposure as its surrounding promotes fast traffic of human movement due to its easy flow of circulation.Overcrowding of shopping malls is one of the factors of an individual's preference in choosing which shopping he/she will go. Its high in preference and demand to the population is ideal as it brings more customers to the commercial establishment, hence, its increase in profit. But, commercial establishments cannot control the number of shoppers going in and out of the mall premises and will go beyond its maximum capacity. This phenomena causes overcrowding, and will lead to decrease in preference to shopper's as they will feel uncomfortable with their personal space being invaded. The human movement, hence predicted, can be used to advantage in planning an environment, by locating ingress and egresses, one of which is the building transportation systems namely escalators, and elevators, to strategic points in the system layout that will redefine its concept of space.This undergraduate thesis entitled ""Optimal Location of Building Transportation Systems in Large Scale Shopping Malls in Davao City Using Dijkstra's Algorithm"", aimed towards establishing guidelines that aided in locating escalators and elevators, considering the Space Syntax properties Integration, Connectivity, Intelligibility, and Proximity that is best fit for each of the different shopping mall typology: Leisure and Utilitarian Mall.Space Syntax Analysis, and Dijkstra's Algorithm were used to determine the values of its Space Syntax Properties, and using its values to determine optimal location of building transportation systems that has the best account on all syntactic measures.Results showed that in Intelligibility, Utilitarian malls have higher intelligibility values than Leisure malls because of its straightforward layout, which made the system become predictable. Leisure malls in having complex layouts with high number of low-integrated convex spaces and few direct connections with high-integrated ones, serves entertaining experience of the system with its variation. While Utilitarian malls with consistent average integrated values connected to only at least 2 or less high-integrated convex spaces suggests mall circulation with direct convergence to one or two nodes. Lastly, integration values on Utilitarian malls have lesser value than the critical value, hence, most of the spaces are shallow and have consistent number of immediate spaces that makes the system more visible, integrated, unlike Leisure malls'These values suggested that building transportation system of Leisure malls with complex layouts should be located in spaces near ingress and egress in deep spaces with low integration values. It will help introduce traffic to low-densed areas of the system, hence, will promote slow traffic in fast-paced movement area, and will suggest shoppers to look around more whilst focused in travelling. On the other hand, Utilitarian malls is suggested to have its building transportation system in spaces with high integrations, that will promote fast traffic in highly populated spaces, that directly serves the users to its purpose of being a utilitarian mall type.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2018